If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(x + -3) = 7 Reorder the terms: -2(-3 + x) = 7 (-3 * -2 + x * -2) = 7 (6 + -2x) = 7 Solving 6 + -2x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -2x = 7 + -6 Combine like terms: 6 + -6 = 0 0 + -2x = 7 + -6 -2x = 7 + -6 Combine like terms: 7 + -6 = 1 -2x = 1 Divide each side by '-2'. x = -0.5 Simplifying x = -0.5
| x+3y=760 | | .5(6x+4)=2(x+1) | | T^2-4t+20=0 | | Z^2-3z-28=0 | | 18x^3-14x^2+45x-35=0 | | x+x+2+4=-207 | | 3x-2=27x+6 | | 3x+y=32 | | 3x+2=7x+18 | | 14y-7n=122 | | 2.5+3.5m=5.5+2m | | y=3x^3-10x+5 | | 8z-12-3z+2=0 | | X^3-8x+7=0 | | 2(-10)+3y-4=x+4 | | 14x^2+45x-22=0 | | 2(0)-3y-6=0 | | 2x+5(2)=15 | | x^3+2x^2+4x-24=0 | | 7(-1x-5)=-77 | | x^10+3=3 | | x^10+3=1 | | -3y=12x+6 | | 72=9y | | -3(2x+9)=-15 | | -5x^2+9x-2=0 | | 10-5x=22x+18 | | 3x+4=5x+5 | | -3(t-4)-(t+1)=9 | | -(6x-6y-7)= | | y=-3(4)+7 | | 10=x*9+6 |